2017
DOI: 10.3310/hta21530
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled study of the effectiveness of breathing retraining exercises taught by a physiotherapist either by instructional DVD or in face-to-face sessions in the management of asthma in adults

Abstract: BackgroundAsthma control is suboptimal, resulting in quality of life (QoL) impairment and costs. Breathing retraining exercises have evidence of effectiveness as adjuvant treatment, but are infrequently used.ObjectivesTo transfer the contents of a brief (three-session) physiotherapist-delivered breathing retraining programme to a digital versatile disc (DVD) and booklet format; to compare the effectiveness of the self-guided intervention with that of ‘face-to-face’ physiotherapy and usual care for QoL and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The economic assessment is reported in detail elsewhere, 14 but showed that both interventions were better than usual care (ie, they resulted in superior outcomes at lower total cost). This finding applied both to AQLQ and quality-adjusted life-year (QALY) comparisons but only the improvement in AQLQ was significant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The economic assessment is reported in detail elsewhere, 14 but showed that both interventions were better than usual care (ie, they resulted in superior outcomes at lower total cost). This finding applied both to AQLQ and quality-adjusted life-year (QALY) comparisons but only the improvement in AQLQ was significant.…”
Section: Resultsmentioning
confidence: 99%
“…In our pragmatic randomised trial, we confirmed that three sessions of face-to-face physiotherapist-taught breathing exercises improve disease-related quality of life for adults with asthma, and we have also shown that equivalent improvements can be achieved from a self-guided digital audiovisual programme. This programme was cost-effective 14 and was considered to be an acceptable intervention method by patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations